Commons becoming non-commons in the efforts for reconciliation between conservation and livelihoods: A case study of northern Pakistan - Khan, S.R.; Rahman, S.A.; Sunderland, Terry C.H. (2011)
The paper examines the impact of converting previous open-access common land into protected areas on the community resource management system in Shimshal, northern Pakistan. We explored three main questions in this regard. First, what happens to community resource management under strict government control of the resource? Secondly, what has happened to the centuries-old practice of the traditional yak herding system of the Shimshal community as a result of the introduction of new policies leading to the creation of protected areas? Thirdly, can the community retain resource control of the protected area (state property), and how can we conceptualize it under the property regime? The research draws the following three conclusions: (1) a clear divide exists between the local government and the community on resource management and resource use, (2) the Shimshal community relies significantly on yaks for their livelihood, and the imposition of new rules and regulations in protected areas has significantly altered the Shimshal community’s traditional yak herding practices, and (3) community control over resources in protected areas would be a new experiment under the state property regime. The study concludes that it is possible to bridge the gap between what have been regarded as irreconcilable principles of protected areas and livelihoods. This arrangement needs to be contextualised by giving specific importance to the community and their management practices. The state would achieve its conservation goals by monitoring the local community’s activities and ensuring that their livelihoods and conservation efforts do not negatively affect each other.